Biomechanical factors associated with intraindividual differences in running economy across advanced footwear technology models in long-distance runners - Fohrmann, D.; Schaffarczyk, M.; Menge, C.; Willwacher, S.; Sanchez-Alvarado, A.; Gronwald, T.; Hollander, K. (Sports Medicine - Open, 2026)
Background Advanced footwear technology (AFT) can enhance long-distance running performance by improving running economy (RE). However, the range of the individual improvements is large. Different intra-individual responses in running biomechanics may account for some of the variation. Thus, this randomized within-subject crossover study aimed to identify biomechanical factors associated with changes in RE when running with different AFT models.